Kinetics and Mechanism of the Thermal Decomposition of Schiff Base Complexes of Cobalt and Nickel by TG and DSC Studies - N.L., Mary; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
The thermal decomposition of cobalt(II) and nickel(II) chelates of dibenzoylmethane thiosemicarbazone (DBMTSC) was studied by TG and DSC studies. The mechanism of the decomposition has been established from TG data. The kinetic parameters, viz., activation energy E, preexponential factor A, and order of reaction n, were calculated from the TG curves using mechanistic and non-mechanistic integral equations.